Enron and the 12 steps of white-collar crime. (11th December 2014) - Appel, Randy; Fratzl, Jae; McKay, Ruth B.; Stevens, Carey
In 2001, Enron Corporation (Enron) filed for Chapter 11 bankruptcy protection due to accounting irregularities. At the core of the failure was a corporate culture that held in contempt regulatory oversight, financial disclosure and the governance process. This paper applies a 12-step model of white-collar crime (McKay et al., 2010) to the case of Enron. The analysis is based on an interview with Sherron Watkins, whistleblower and former employee of Enron, as well as other coverage of the Enron collapse. This paper presents the value of the model as applied to a single organisation and makes recommendations based on the application.